Water Fountain, Horniman Circle Garden - Ghosh, Ayan (2023)
Ongoing restoration work at the water fountain at Horniman Circle Garden. Earlier, the garden used to house statues of British administrators and military heroes like Richard Wellesley, 1st Marquess Wellesley, and Charles Cornwallis, 1st Marquess Cornwallis which were later removed and relocated to the Veermata Jijamata Udyaan in Byculla.